THE EFFECT OF AUDITEE CHARACTERISTICS AND PUBLIC ACCOUNTING FIRM SIZE ON ABNORMAL AUDIT REPORT LAG - Kahirul Umam; Yudhi Herliansyah (JRAK, 2023)
This research aims at determining a more specific relationship regarding the influence of firm size, profitability, solvency, and KAP size variables that affected the probability of Abnormal Audit Report Lag. The research used secondary data from financial and independent auditor reports obtained from the Indonesia Stock Exchange Consumer Goods Industry Companies for the 2018-2020 period. The total sample in this research was 167 and the data analysis method used was multinomial logistic regression analysis. The results of this research proved that company size and public accountant size could significantly affect audit report lag. Meanwhile, Profitability and Solvability had no significant effect on Abnormal Audit Report Lag.